Systematic review of the prevalence of suicide in veterinary surgeons. - Platt, B; Hawton, K; Simkin, S; Mellanby, R (2010)
BACKGROUND: An accumulating body of research demonstrates that risk of suicide varies between occupational groups. Identification of the occupations at risk, and the factors that contribute to the increased risk of suicide in these groups is essential for the development of effective suicide prevention strategies. There is preliminary evidence to suggest that veterinary surgeons are a group at risk. AIMS: To conduct a systematic review of studies of rates and methods of suicide in the veterinary profession. METHODS: A systematic search of the international research literature was performed in May 2008. The data from the 19 studies of the prevalence of suicide in the veterinary profession were extracted by two independent reviewers and analysed. RESULTS: Between 0 and 43% of veterinary surgeon deaths were due to suicide. In all but one of the 15 studies presenting risk of suicide in veterinary surgeons with a comparison population, an elevated risk was found. The better quality studies with the lowest risk of bias indicated that in the UK, the rate of suicide in the veterinary profession was at least three times the general population rate. Studies of the methods of suicide veterinary surgeons use suggest that self-poisoning and firearms are particularly common. CONCLUSIONS: There appears to be an elevated risk of suicide for veterinary surgeons in several countries. Access to means of suicide influences the methods used and may contribute to increased risk.